Dynamics of vehicles on roads and tracks : proceedings of the 24th International Symposium on Dynamics of Vehicles on Roads and Tracks (IAVSD 2015), August 17-21 2015, Graz, Austria /: proceedings of the 24th International Symposium on Dynamics of Vehicles on Roads and Tracks (IAVSD 2015), August 17-21 2015, Graz, Austria. (2016) - Unknown
No abstract available